Acute Occlusion of Brachial Artery Caused by Blunt Trauma in Football Player: Case Report and Review of the Literature. Issue 6 (November 2017) - Chan, John; Han, David; Gallo, Robert A.
Abstract : A football player sustained blunt trauma to the brachial artery resulting in thrombosis which resolved without the need for operative intervention.